Rethinking the area approach: Immigrants and the labor market in California, 1960-2005 - Giovanni Peri (University of California, Department of Economics, 2009)
A series of recent influential papers has emphasized that in order to identify the wage effects of immigration one needs to consider national effects by skill level. The criticism to the so called ,,area approach“ is based on the fact that native workers are mobile and would eliminate, in the long-run, local wage effects in a national market. A second criticism is that the small sizes of many local labor markets induces large measurement errors in the share of immigrants and attenuation bias in the estimates of their effects. In this paper we show that a roduction-function-based approach with skill differentiation and integrated national markets has predictions on the employment effect of immigrants at the local (state) level. Hence if we look at the employment (rather than wage) response to immigration by state, we can still estimate the substitutability-complemetariety between natives and immigrants and infer whether, other things constant, immigrants stimulate or depress the demand for native labor. Moreover, to avoid measurement error issues, we only consider California, as it is the largest state and the largest recipient of immigrants. To address further endogeneity issues we use demographic characteristics of Mexican migrants to the US to predict immigration by skill level in California. Looking at immigraton between 1960 and 2005 we find that: i) the assumption of a national integrated labor market by skill holds and ii) immigration did not have any negative employment effect on natives in any education-experience group in California. The estimated effects support the hypothesis that natives and immigrants in the same education-experience group are not perfectly substitutable. Specializing in different tasks and stimulating efficiency are the other likely mechanisms through which immigrants stimulate (rather than hurt) employment of natives.
Keywords: F22; J61; J31; R13; 330; immigration; native employment; inter-state migration; complementariety; Arbeitsmarkt; Migranten; Qualifikation; Arbeitsnachfrage; Lohnniveau; Kalifornien